Effects of inspiratory muscle training on 1RM performance and body composition in professional natural bodybuilders - Baha Engin Çelikel; Coşkun Yılmaz; Alper Demir; Süreyya Yonca Sezer; Levent Ceylan; Tülay Ceylan; Çetin Tan (Frontiers in Physiology)
BackgroundThe effect of inspiratory muscle training on upper limbs One Rep Maximum (1RM) in professional natural bodybuilders is still unclear. Our aim of this study is to investigate the effects of a 6 weeks inspiratory muscle training on 1RM results.MethodsThis study included 14 athletes, that had participated in international bodybuilding competitions. Each athlete had been training for minimum of 5 years and at least 5 h per week. The participants were randomly divided into two groups: inspiratory muscle training (IMT) and control (CON) groups. The IMT group and CON group consisted of seven subjects. While the control group continued with the normal training regime, the IMT group additionally performed inspiratory muscle training with the resistance setting of the PowerBreathe® Classic device set to 40% of the participant’s MIP. Prior to and during the 6-week training period, the bench press 1 RM, anthropometry, pulmonary function tests, and maximal inspiratory (MIP) and expiratory (MEP) pressure measurements were obtained. A nutrition protocol developed by a qualified dietician was implemented for each athlete.ResultsThe mean maximal strength of the respiratory muscle training group changed by 14.39%, whereas that of the control group changed by 9.43% (p = 0.012). The changes in the mean FVC (p = 0.000), FEV1 (p = 0.001), PEF (p = 0.064), MIP (p = 0.001), and maximal expiratory pressure (p = 0.017) were greater in the IMT group. The mean circumferences of the shoulder (p = 0.004), chest (p = 0.008), arm (p = 0.004), and neck (p = 0.003) improved more in the IMT group than in the CON group. A reduction in abdominal measurement was observed in the IMT group (p = 0.039), whereas no notable discrepancy was identified in body fat percentage (p = 0.295).ConclusionIn conclusion we identified that the addition of progressive loading inspiratory muscle training for competition preparation programs in professional natural bodybuilders will further improve their respiratory function, respiratory muscle strength, maximal strength, and muscle development. This research provides valuable insights into how IMT influences bodybuilding training outcomes, potentially guiding future interventions and program designs to better support strength development and body composition in bodybuilding training contexts.